Crankshaft preform and method for producing crankshaft preform

A crankshaft material with a tailored chemical composition and optimized ferrite-pearlite structure, processed through specific forging techniques, addresses the challenges of abrasion resistance, machinability, and fatigue strength without induction hardening, achieving superior performance.

JP2025043994APending Publication Date: 2025-04-01NIPPON STEEL CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023151635
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing crankshaft materials face challenges in achieving excellent abrasion resistance, machinability, and fatigue strength without induction hardening, and there is a need to improve mechanical properties without relying on expensive elements like vanadium.

Method used

A crankshaft material with a specific chemical composition (C: 0.35-0.50%, Si: 0.75-2.50%, Mn: 1.00-1.50%, Cr: 0.30% or less, P: 0.030% or less, S: 0.020-0.100%, Al: 0.500% or less, N: 0.002-0.020%, V: 0-0.20%, Ti: 0-0.050%, Ca: 0-0.010%) and a ferrite-pearlite structure, optimized through a billet forging and mold forging process with controlled heating and cooling rates, to enhance Mn solubility and proeutectoid ferrite volume fraction.

Benefits of technology

The material achieves excellent abrasion resistance, machinability, and fatigue strength even without induction hardening, with improved wear resistance and machinability due to enhanced Mn solubility and proeutectoid ferrite content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043994000001_ABST
    Figure 2025043994000001_ABST
Patent Text Reader

Abstract

To provide a crankshaft preform which exhibits excellent wear resistance and excellent machinability even when used without high-frequency quenching.SOLUTION: A crankshaft preform has a predetermined chemical composition, with Fn1 as defined by the following formula (1) being 5.10 or more and 6.00 or less. The structure includes 5.0 to 18.0 vol.% of proeutectoid ferrite, and the remainder is pearlite. At a position 50 μm deep from the surface of the portion corresponding to the pin portion of a crankshaft, the ratio Mnθ / Cθ, which is obtained by analyzing the Mn content Mnθ and the C content Cθ in the cementite in the pearlite by energy-dispersive X-ray analysis, is 0.36 or more. Fn1=7C+0.5Si+Mn+3Cr-10Ti (1). In the formula (1), C, Si, Mn, Cr, and Ti are substituted with the content of the corresponding elements in mass%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a preform for a crankshaft and a method for manufacturing the preform for a crankshaft. In this specification, the term "preform for a crankshaft" refers to an intermediate product that has been machined into a shape close to that of a final product, that is, a crankshaft. [Background technology]

[0002] Crankshafts used in automobile engine parts are generally induction-hardened on the sliding parts, the pins and journals. Induction hardening forms a high-hardness structure, such as martensite, on the surface of the pins and journals, improving their wear resistance. On the other hand, crankshafts that do not undergo induction hardening are also used, mainly for the purpose of reducing costs. In mechanical structural carbon steels and mechanical structural alloy steels, steels that do not undergo thermal treatments such as quenching and tempering are called "non-tempered steels."

[0003] JP 2003-201536 A discloses a non-heat treated steel for hot working having excellent wear resistance. This non-heat treated steel for hot working contains 0.32-0.6 mass% C, 0.05-1.5 mass% Si, 0.30-2.0 mass% Mn, 0.01 mass% or less Al, 1.5 mass% or less Cr, and 0.01-0.5 mass% V, and is characterized in that the structure after hot working is a ferrite-pearlite structure with a ferrite area ratio of more than 0% and 35% or less, and the hardness of the ferrite part is 170-270 HV.

[0004] The crankshaft preform is subjected to machining such as grinding and drilling. Therefore, it is preferable that the crankshaft preform has excellent machinability. Japanese Patent Application Laid-Open Nos. 2000-282172 and 2001-214241 disclose steel materials for machine construction with excellent machinability. These steel materials for machine construction have a predetermined chemical composition, and 10 to 80% of the structure is a ferrite phase. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2003-201536 A [Patent Document 2] JP 2000-282172 A [Patent Document 3] JP 2001-214241 A Summary of the Invention [Problem to be solved by the invention]

[0006] One method for improving the wear resistance of steel is to increase the C content to increase the hardness of the steel. However, increasing the C content is in a trade-off relationship with the machinability of the steel. In addition, the addition of precipitation hardening elements such as V has been carried out as a method for improving the mechanical properties of non-tempered steel, but since V is a relatively expensive element, it is preferable to improve the mechanical properties of steel by a method other than the addition of V.

[0007] An object of the present invention is to provide a crankshaft material having excellent wear resistance even when used without induction hardening, and also having excellent machinability and excellent fatigue strength. [Means for solving the problem]

[0008] The crankshaft material according to one embodiment of the present invention has a chemical composition, in mass%, of C: 0.35-0.50%, Si: 0.75-2.50%, Mn: 1.00-1.50%, Cr: 0.30% or less, P: 0.030% or less, S: 0.020-0.100%, Al: 0.500% or less, N: 0.002-0.020%, V: 0-0.20%, Ti: 0-0.050%, Ca: 0-0.0 10%, the balance being Fe and impurities, Fn1 defined by the following formula (1) is 5.10 to 6.00, the structure contains 5.0 to 18.0 volume% pro-eutectoid ferrite, the balance being pearlite, and the Mn content Mn obtained by analyzing cementite in the pearlite at a position at a depth of 50 μm from the surface of a portion corresponding to a pin portion of a crankshaft by energy dispersive X-ray analysis is θ and C content C θ Relative to Mn θ / C θ is 0.36 or more. Fn1=7C+0.5Si+Mn+3Cr-10Ti (1) In formula (1), the contents of the corresponding elements, C, Si, Mn, Cr, and Ti, are substituted in mass%. The energy dispersive X-ray analysis is carried out on C, Mn, Cr, V and Fe. θ and C θ Each of the above is a value calculated in mass % with the sum of C, Mn, Cr, V and Fe as the denominator.

[0009] A manufacturing method of a crankshaft base material according to one embodiment of the present invention is a method for manufacturing the above-mentioned crankshaft base material, and includes a billet forging process in which a slab produced by a continuous casting method is hot forged to form a billet, and a die forging process in which the billet is hot forged. In the hot forging in the billet forging process, the heating temperature before hot forging is 1150 to 1300°C and the holding time at the heating temperature is 3.0 hours or more. In the hot forging in the die forging process, the heating temperature before hot forging is 1200 to 1350°C and the heating time to the heating temperature is 500 seconds or less. The average cooling rate in the temperature range of 750 to 600°C after forging is 0.5°C / second or less. Effect of the Invention

[0010] According to the present invention, it is possible to obtain a crankshaft preform having excellent wear resistance even when used without induction hardening, and also having excellent machinability and excellent fatigue strength. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a scatter diagram showing the relationship between Fn1 and the pro-eutectoid ferrite volume fraction Fα. [Diagram 2] FIG. 2 is a scatter diagram showing the relationship between Fn1 and the amount of flank wear. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present inventors have conducted various studies to solve the above problems and have obtained the following findings.

[0013] Crankshaft preforms are manufactured by hot forging billets of a specified size. Crankshaft preforms manufactured by hot forging have a structure consisting of ferrite and pearlite. In order to improve the wear resistance of the hot forged structure, i.e., the ferrite-pearlite structure, it is effective to increase the amount of Mn dissolved in the cementite in pearlite.

[0014] A billet, which is a raw material for a crankshaft blank, is produced, for example, by hot forging or hot rolling from a slab produced by a continuous casting method. In a slab produced by a continuous casting method, Mn tends to be concentrated near the center of the slab due to solidification of molten steel from the surface. Therefore, in a billet produced from this slab, Mn may also be concentrated near the center, and in a crankshaft blank produced from this billet, Mn may also be concentrated near the center.

[0015] On the other hand, since it is the properties near the surface that contribute to wear resistance, it is preferable for a sufficient amount of Mn to be present near the surface of the crankshaft material in order to improve the wear resistance of the crankshaft material.

[0016] In order to ensure that a sufficient amount of Mn is present in the vicinity of the surface of a crankshaft preform, it is effective to heat the billet for a long period of time to sufficiently diffuse the Mn, and then perform hot forging to eliminate center segregation in the billet. From the viewpoint of diffusing Mn, it is possible to extend the heating time when producing a crankshaft preform from the billet, but as will be described later, extending this heating time makes it difficult to obtain the desired structure.

[0017] In order to improve the machinability of crankshaft preforms, it is effective to increase the volume fraction of pro-eutectoid ferrite in the ferrite-pearlite structure. In order to increase the volume fraction of pro-eutectoid ferrite, it is effective to control the chemical composition of the steel and increase the heating rate before hot forging when manufacturing crankshaft preforms from billets. Specifically, it is effective to start hot forging immediately after rapid heating by high-frequency induction heating. This suppresses the grain growth of austenite grains in the high temperature range. By making the austenite grains smaller, the area of ​​the grain boundaries that become the precipitation sites of pro-eutectoid ferrite becomes larger, and the amount of pro-eutectoid ferrite can be increased.

[0018] In order to improve the fatigue strength of crankshaft materials with a ferrite-pearlite structure, it is effective to increase the content of Si, a ferrite strengthening element. On the other hand, if the Si content is increased, the timing of cementite precipitation during cooling after forging is delayed, and Mn may not be sufficiently dissolved in the cementite in the pearlite. When the Si content is increased, it is effective to reduce the cooling rate in the temperature range where pearlite is formed (specifically, 750 to 600°C) in order to obtain an appropriate structure in which Mn is sufficiently dissolved in the cementite in the pearlite.

[0019] The present invention has been completed based on the above findings. A crankshaft preform according to one embodiment of the present invention will now be described in detail.

[0020] [Crankshaft materials] [Chemical composition] The crankshaft preform according to this embodiment has the chemical composition described below. In the following description, "%" for the content of an element means mass %.

[0021] C: 0.35-0.50% Carbon (C) improves the hardness of steel and contributes to improving fatigue strength and wear resistance. On the other hand, if the C content is too high, the machinability decreases. Therefore, the C content is 0.35 to 0.50%. The lower limit of the C content is preferably 0.37%, more preferably 0.40%, and more preferably 0.42%. The upper limit of the C content is preferably 0.48%, and more preferably 0.45%.

[0022] Silicon: 0.75 to 2.50% Silicon (Si) has a deoxidizing effect and an effect of strengthening ferrite. In the crankshaft preform according to the present embodiment, the Si content is set high in order to obtain the ferrite strengthening effect of Si. On the other hand, if the Si content is too high, the machinability of the steel decreases. Therefore, the Si content is 0.75 to 2.50%. The lower limit of the Si content is preferably 0.90%, more preferably 1.20%, more preferably 1.60%, and even more preferably 1.80%. The upper limit of the Si content is more preferably 2.30%, and even more preferably 2.10%.

[0023] Mn: 1.00-1.50% Manganese (Mn) improves the hardness of steel and contributes to improving fatigue strength and wear resistance. Mn also dissolves in cementite in pearlite and has the effect of strengthening pearlite. On the other hand, if the Mn content is too high, the machinability of the steel decreases. Therefore, the Mn content is 1.00 to 1.50%. The lower limit of the Mn content is preferably 1.10%, and more preferably 1.20%. The upper limit of the Mn content is preferably 1.40%, and more preferably 1.35%.

[0024] Cr:0.30% or less Chromium (Cr) improves the hardness of steel and contributes to improving fatigue strength and wear resistance. On the other hand, if the Cr content is too high, the machinability of the steel decreases. Therefore, the Cr content is 0.30% or less. The lower limit of the Cr content is preferably 0.01%, more preferably 0.05%, and more preferably 0.08%. The upper limit of the Cr content is preferably 0.25%, and more preferably 0.20%.

[0025] P:0.030% or less Phosphorus (P) is an impurity. P reduces the hot workability of steel. Therefore, the P content is 0.030% or less. The P content is preferably 0.025% or less, and more preferably 0.020% or less.

[0026] S: 0.020~0.100% Sulfur (S) forms MnS and improves the machinability of steel. On the other hand, if the S content is too high, the hot workability of steel decreases. Therefore, the S content is 0.020 to 0.100%. The lower limit of the S content is preferably 0.030%, and more preferably 0.040%. The upper limit of the S content is preferably 0.080%, and more preferably 0.070%.

[0027] Al: 0.500% or less Aluminum (Al) has a deoxidizing effect. On the other hand, if the Al content is too high, the machinability of the steel decreases. Therefore, the Al content is 0.500% or less. The lower limit of the Al content is preferably 0.005%, more preferably 0.010%, and more preferably 0.020%. The upper limit of the Al content is preferably 0.200%, more preferably 0.100%, and more preferably 0.050%.

[0028] N: 0.002~0.020% Nitrogen (N) forms nitrides and carbonitrides, and contributes to the refinement of crystal grains (austenite grains) in high temperature regions. The refinement of austenite grains increases the area of ​​grain boundaries that become the precipitation sites of pro-eutectoid ferrite, resulting in an increase in the amount of pro-eutectoid ferrite. In addition, excessive reduction of N increases the manufacturing cost. On the other hand, if the N content is too high, the hot workability of the steel decreases. Therefore, the N content is 0.002 to 0.020%. The lower limit of the N content is preferably 0.005%. The upper limit of the N content is preferably 0.015%, and more preferably 0.012%.

[0029] The balance of the chemical composition of the crankshaft preform according to the present embodiment is Fe and impurities. The impurities referred to here are elements that are mixed in from ores or scraps used as raw materials for steel, or elements that are mixed in from the manufacturing process environment, etc.

[0030] The chemical composition of the crankshaft preform according to this embodiment may contain one or more elements selected from V, Ti, and Ca in place of a portion of Fe. V, Ti, and Ca are optional elements. In other words, the chemical composition of the crankshaft preform according to this embodiment may not contain some or all of V, Ti, and Ca.

[0031] V: 0~0.20% Vanadium (V) enhances the wear resistance of steel by precipitation hardening. This effect can be obtained even if even a small amount of V is contained. The crankshaft preform according to this embodiment improves the wear resistance by a method other than the addition of V. Therefore, the crankshaft preform according to this embodiment does not need to contain V. Not containing V is advantageous in terms of cost. On the other hand, V may be contained as necessary. However, if the V content is too high, the machinability of the steel decreases. Therefore, the V content is 0 to 0.20%. The lower limit of the V content is preferably 0.02%, more preferably 0.08%. The upper limit of the V content is preferably 0.15%, more preferably 0.12%. From the viewpoint of production cost, the upper limit of the V content is preferably 0.10%, more preferably 0.08%, and more preferably 0.05%. From the viewpoint of production cost, it is most preferable not to contain V.

[0032] Ti: 0 to 0.050% Titanium (Ti) forms nitrides and carbonitrides, and contributes to the refinement of crystal grains (austenite grains) in high temperature regions. By refining the austenite grains, the area of ​​grain boundaries that become the precipitation sites of pro-eutectoid ferrite increases, resulting in an increase in pro-eutectoid ferrite. On the other hand, even if Ti is added in excess, the effect saturates and causes an increase in costs. Therefore, the Ti content is 0 to 0.050%. The lower limit of the Ti content is preferably 0.001%, and more preferably 0.005%. The upper limit of the Ti content is preferably 0.040%, more preferably 0.030%, and more preferably 0.020%.

[0033] Ca: 0 to 0.010% Calcium (Ca) improves the hot workability of steel. This effect can be obtained even if even a small amount of Ca is contained. Therefore, Ca may be contained as necessary. On the other hand, if the Ca content is too high, the toughness of the steel decreases. Therefore, the Ca content is 0 to 0.010%. The lower limit of the Ca content is preferably 0.001%. The upper limit of the Ca content is preferably 0.008%, and more preferably 0.006%.

[0034] [About Fn1] In the crankshaft preform according to the present embodiment, Fn1 defined by the following formula (1) is 5.10 or more and 6.00 or less. Fn1=7C+0.5Si+Mn+3Cr-10Ti (1) In formula (1), the contents of the corresponding elements, C, Si, Mn, Cr, and Ti, are substituted in mass%.

[0035] Fn1 is a parameter that correlates with the volume fraction of pro-eutectoid ferrite. The smaller Fn1 is, the larger the volume fraction of pro-eutectoid ferrite is. If Fn1 is less than 5.10 or more than 6.00, it becomes difficult to set the volume fraction of pro-eutectoid ferrite within an appropriate range. The lower limit of Fn1 is preferably 5.20, more preferably 5.30, and even more preferably 5.70. The upper limit of Fn1 is preferably 5.90.

[0036] [Organization] The crankshaft preform according to this embodiment has a structure containing 5.0 to 18.0 volume % of pro-eutectoid ferrite, with the remainder being pearlite.

[0037] The structure of the crankshaft preform according to this embodiment is a ferrite-pearlite structure. That is, the crankshaft preform according to this embodiment has a structure consisting of pro-eutectoid ferrite and pearlite. Pearlite is a structure in which ferrite and cementite form a fine layered structure (pearlite lamella), and pro-eutectoid ferrite means ferrite that precipitates from prior austenite grain boundaries, separate from the ferrite in the pearlite lamella.

[0038] The structure of the crankshaft preform according to this embodiment has a pro-eutectoid ferrite volume fraction of 5.0 to 18.0%. If the pro-eutectoid ferrite volume fraction is too low, good machinability cannot be obtained. On the other hand, if the pro-eutectoid ferrite volume fraction is too high, fatigue strength may decrease. The lower limit of the pro-eutectoid ferrite volume fraction is preferably 8.0%, more preferably 10.0%. The upper limit of the pro-eutectoid ferrite volume fraction is preferably 17.0%, more preferably 16.0%.

[0039] It is preferable that the volume fraction of the pro-eutectoid ferrite is set to an amount corresponding to the Si content. Specifically, it is preferable that the crankshaft preform according to this embodiment satisfies the following formula (2). Fα<0.875×Si+14.344 (2) In formula (2), the volume fraction of pro-eutectoid ferrite in % is substituted for Fα, and the Si content in mass % is substituted for Si.

[0040] The crankshaft preform according to the present embodiment preferably satisfies the following formula (3). Fα<-16.059×Fn1+112.0 (3) In formula (3), the volume fraction of pro-eutectoid ferrite is substituted for Fα in percentage.

[0041] [Mn θ / C θ ] The crankshaft preform according to the present embodiment has a Mn content of Mn obtained by analyzing cementite in pearlite by energy dispersive X-ray analysis at a depth of 50 μm from the surface of a portion corresponding to a pin portion of the crankshaft. θ and C content C θ Relative to Mn θ / C θ The energy dispersive X-ray analysis is carried out for C, Mn, Cr, V and Fe, and Mn θ and C θ Each of the above is a value calculated in mass % with the sum of C, Mn, Cr, V and Fe as the denominator.

[0042] In order to improve the wear resistance of the ferrite-pearlite structure, it is effective to increase the amount of Mn dissolved in the cementite in the pearlite. The part near the surface of the crankshaft material contributes to wear resistance. Therefore, in order to improve wear resistance, it is preferable to increase the amount of Mn dissolved in the cementite in the pearlite near the surface.

[0043] In this embodiment, the position of 50 μm deep from the surface of the part corresponding to the pin part of the crankshaft is evaluated, and the cementite in the pearlite present at this position is analyzed by energy dispersive X-ray analysis (EDX). Specifically, the part corresponding to the pin part of the crankshaft is cut so that the cut surface is a plane perpendicular to the axial direction of the pin part, and the cut surface is observed by a scanning electron microscope (SEM) at a magnification of about 10,000 times. While checking the SEM image, the cementite in the pearlite is irradiated with an electron beam and the chemical composition of the cementite is analyzed by EDX. The reason why C, Mn, Cr, V, and Fe are analyzed is that it is unlikely that elements other than these are solid-dissolved in cementite, and even if they are present, the amount is small and it is considered that they do not affect the characteristics.

[0044] In this embodiment, the Mn content Mn obtained from the analysis result θ and C content C θ Relative to Mn θ / C θ The amount of Mn dissolved in cementite in pearlite near the surface is evaluated by the following method. θ / C θ If the Mn content is 0.36 or more, excellent wear resistance is obtained. θ / C θ The lower limit of Mn is preferably 0.38, more preferably 0.40, more preferably 0.45, more preferably 0.50, and even more preferably 0.55. θ / C θ The upper limit of is not particularly limited, but is, for example, 2.00, preferably 1.50, more preferably 1.20, more preferably 1.00, and more preferably 0.80.

[0045] [Manufacturing method of crankshaft blanks] Next, an example of a method for manufacturing the crankshaft preform according to this embodiment will be described. The manufacturing method described below is merely an example and does not limit the manufacturing method of the crankshaft preform according to this embodiment.

[0046] The crankshaft preform according to this embodiment can be manufactured by hot forging a slab produced by continuous casting to form a billet, and then hot forging the billet. Hereinafter, the hot forging used to produce a billet from a slab is referred to as "billet forging", and this process is referred to as the billet forging process. In addition, the hot forging used to produce a crankshaft preform from a billet is referred to as "die forging", and this process is referred to as the "die forging process".

[0047] [Billet forging process] First, a slab of steel produced by continuous casting of molten steel having the above-mentioned chemical composition is hot forged into a billet of a size suitable for die forging (billet forging process).

[0048] In the hot forging (billet forging) in the billet forging process, the heating temperature before forging is set to 1150 to 1300°C, and the holding time at the heating temperature is set to 3.0 hours or more. By holding at a high temperature for a long time before forging, Mn segregated in the center of the slab is diffused. If the heating temperature is too low or the holding time is too short, the diffusion of Mn may be insufficient. On the other hand, if the heating temperature is too high, the slab may partially melt. The lower limit of the heating temperature in the billet forging process is preferably 1180°C. The upper limit of the heating temperature in the billet forging process is preferably 1280°C, more preferably 1260°C. The lower limit of the holding time at the heating temperature in the billet forging process is preferably 4.0 hours, more preferably 4.5 hours. The upper limit of the holding time at the heating temperature is not particularly limited, but is, for example, 8.0 hours, preferably 6.0 hours.

[0049] After being held at the heating temperature, the slab is forged into a billet of a predetermined size. At this time, it is preferable that the final area reduction rate ({(cross-sectional area of ​​slab)-(cross-sectional area of ​​billet)} / (cross-sectional area of ​​slab)) is 90% or more. The area reduction rate is more preferably 92% or more, and even more preferably 94% or more. The billet to be produced is preferably a billet with a circular cross section (round billet).

[0050] After the forging is completed, the material is cooled to room temperature. The cooling rate is not particularly limited, but is preferably 300° C. / hour or less, and more preferably 250° C. / hour or less.

[0051] [Die forging process] Next, the billet produced in the billet forging process is hot forged into a crankshaft blank (die forging process).

[0052] In the hot forging (die forging) in the die forging process, the heating temperature before forging is set to 1200 to 1350°C. If the heating temperature is too low, it may be difficult to process into a complex shape. On the other hand, if the heating temperature is too high, the billet may partially melt. The lower limit of the heating temperature is preferably 1230°C, more preferably 1250°C. The upper limit of the heating temperature is preferably 1325°C, more preferably 1300°C.

[0053] In die forging, the heating time to the heating temperature (the time from the start of heating to the heating temperature) is set to 500 seconds or less. Such rapid heating can be achieved, for example, by a high-frequency induction heating device. By heating the billet to the heating temperature in a short time, the grain growth of austenite grains is suppressed. By making the austenite grains smaller, the area of ​​the grain boundaries that become the precipitation sites of pro-eutectoid ferrite is increased, and the amount of pro-eutectoid ferrite can be increased. The upper limit of the heating time to the heating temperature is preferably 400 seconds, and more preferably 320 seconds. The lower limit of the heating time to the heating temperature is not particularly limited, but is, for example, 100 seconds, and preferably 200 seconds.

[0054] After the heating temperature is reached, forging is started immediately. The forging start temperature (surface temperature of the billet just before the start of forging) is preferably (heating temperature -150°C) or higher, and more preferably (heating temperature -100°C) or higher.

[0055] The billet is forged into a shape close to that of the final crankshaft. This forging (rough forging) may be followed by finish forging.

[0056] After forging, the billet is cooled to room temperature. In this embodiment, the average cooling rate in the temperature range of 750 to 600°C is set to 0.5°C / sec or less. The billet described above contains a large amount of Si. Si has the effect of delaying the precipitation of cementite. If the temperature is lowered before cementite has sufficiently precipitated, Mn may not be sufficiently dissolved in the cementite in pearlite.

[0057] By setting the average cooling rate in the temperature range of 750 to 600°C, which is the temperature range in which pearlite is formed, to 0.5°C / sec or less, an appropriate structure in which Mn is sufficiently dissolved in the cementite in pearlite can be obtained. The lower limit of the average cooling rate in the temperature range of 750 to 600°C is not particularly limited, but is, for example, 0.1°C / sec.

[0058] There are no particular limitations on the cooling rate in a temperature range other than 750 to 600° C. The average cooling rate in a temperature range of 600° C. or less is preferably 5° C. / sec or less, and more preferably 2° C. / sec or less.

[0059] Through the above steps, a crankshaft blank is manufactured.

[0060] An example of a crankshaft preform according to one embodiment of the present invention and a method for producing the same have been described above. The crankshaft preform according to this embodiment is machined, such as by grinding and drilling, to become a crankshaft, which is a final product. The crankshaft preform according to this embodiment has excellent machinability. Furthermore, the crankshaft preform according to this embodiment has excellent wear resistance even when used without induction hardening.

[0061] [Crankshaft] A crankshaft according to one embodiment of the present invention is a crankshaft manufactured from the above-mentioned crankshaft preform. Of the crankshafts manufactured from the above-mentioned crankshaft preform, those that are used without induction hardening are particularly preferred. That is, a crankshaft according to one embodiment of the present invention is a crankshaft that is used without induction hardening, and has a chemical composition, in mass%, of C: 0.35-0.50%, Si: 0.75-2.50%, Mn: 1.00-1.50%, Cr: 0.30% or less, P: 0.030% or less, S: 0.020-0.100%, Al: 0.500% or less, N: 0.002-0.020%, V: 0-0.20%, Ti: 0-0.002% and the like. The composition is as follows: 0.050%, Ca: 0-0.010%, the balance: Fe and impurities, Fn1 defined by the following formula (1) is 5.10 to 6.00, the structure contains 5.0-18.0 volume% pro-eutectoid ferrite, the balance being pearlite, and the Mn content Mn obtained by analyzing cementite in the pearlite at a depth of 50 μm from the surface of a portion corresponding to a pin portion of a crankshaft by energy dispersive X-ray analysis is θ and C content C θ Relative to Mn θ / C θ is 0.36 or more. Fn1=7C+0.5Si+Mn+3Cr-10Ti (1) In formula (1), the contents of the corresponding elements, C, Si, Mn, Cr, and Ti, are substituted in mass%. The energy dispersive X-ray analysis is carried out on C, Mn, Cr, V and Fe. θ and Cθ Each of the above is a value calculated in mass % with the sum of C, Mn, Cr, V and Fe as the denominator. EXAMPLES

[0062] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0063] Molten steel having the chemical composition shown in Table 1 was cast to produce a slab with a cross section of 400 mm x 530 mm. Note that "Fn2" in Tables 1 and 4 is the right side of formula (2) (=0.875 x Si + 14.344).

[0064] [Table 1]

[0065] These slabs were hot forged (billet forging) to produce round billets with a diameter of 85 mm. The conditions for billet forging are shown in Table 2. In process code c1, only heating was performed without forging, and a round billet with a diameter of 85 mm was produced by machining. In process code d1, a round billet with a diameter of 85 mm was produced by machining the slabs.

[0066] [Table 2]

[0067] The produced billets were hot forged (die forged) to produce crankshaft blanks. The die forging conditions are shown in Table 3. The "heating time" in Table 3 refers to the time from the start of heating to the heating temperature being reached. After the forging shown in Table 3, finish forging was performed with a starting temperature of 1100°C and a finishing temperature of 1070°C.

[0068] [Table 3]

[0069] The portion of the produced crankshaft blank corresponding to the pin portion of the crankshaft (hereinafter simply referred to as the "pin portion") was cut at the center of the parallel portion so that the cut surface was a surface perpendicular to the axial direction of the pin portion. The cut surface was polished and etched using a mixed solution of ethanol and nitric acid (nital). A position 50 μm deep from the surface was observed with an optical microscope at a magnification of 500 times, and the area ratio of pro-eutectoid ferrite was measured. The measured area ratio of pro-eutectoid ferrite was regarded as the volume ratio of pro-eutectoid ferrite.

[0070] The pin portion of the crankshaft blank was cut in the center of the parallel portion so that the cut surface was perpendicular to the axial direction of the pin portion. The cut surface was polished and etched using a mixed solution of ethanol and nitric acid (nital). A position 50 μm deep from the surface was observed at a magnification of about 10,000 times using a scanning electron microscope (SEM). While checking the SEM image, the cementite in the pearlite was irradiated with an electron beam and the chemical composition of the cementite was analyzed by EDX, and Mn was found to be the most abundant. θ and C θ The EDX was used to analyze C, Mn, Cr, V and Fe, and Mn θ and C θ Each of the above was calculated in mass% with the sum of C, Mn, Cr, V and Fe as the denominator. Mn θ and C θ was the average value obtained at eight locations.

[0071] For EDX, a JED-2300 manufactured by JEOL was used. The measurement conditions were an accelerating voltage of 15 kV.

[0072] The wear resistance of the crankshaft preform was evaluated based on the wear diameter of the pin after the wear test. Specifically, a crankshaft manufactured by machining the crankshaft preform was mounted on an engine bench test machine, and a wear test was performed by rotating the engine for 20 hours at 7000 rpm, oil temperature of 110°C, oil pressure of 200 kPa, and low viscosity oil (OW-16), and the change in the diameter of the pin was measured. Before and after the wear test, measurements were taken at three points on the circumference (0°, 120°, and 240° positions) with a micrometer to calculate the average, and the wear diameter was calculated by subtracting the diameter before the wear test from the diameter after the wear test. If the wear diameter was 1.00 μm or less, it was evaluated as having excellent wear resistance.

[0073] The fatigue strength of the crankshaft preform was measured as follows. Ono-type rotating bending fatigue test pieces were taken from the crankshaft preform and subjected to a rotating bending fatigue test in accordance with JIS Z 2274. 7 The maximum stress that did not cause fracture was taken as the fatigue strength. The target fatigue strength was 380 MPa or more.

[0074] The machinability of the crankshaft blank was evaluated as follows. A guide hole 22 mm deep was drilled in the crankshaft blank with a 5 mm diameter guide drill, and then an oil hole 91 mm deep was drilled with a 4.98 mm diameter long drill. Both the guide drill and the long drill were solid drills with a TiN coating and had an oil supply hole inside. After drilling 600 times under specified conditions while supplying oil using the MQL method, the machinability was evaluated by measuring the flank wear of the long drill. Specifically, an enlarged photograph of the outside of the flank was taken with a microscope, and the width of the area showing metallic luster (the area where the coating had peeled off) formed between the coating and the cutting edge was measured, and this width was taken as the flank wear. If the flank wear was 0.040 mm or less, the blank was evaluated as having excellent machinability.

[0075] The results are shown in Table 4. In Table 4, "Fα" represents the volume fraction of pro-eutectoid ferrite.

[0076] [Table 4]

[0077] As shown in Table 4, the crankshaft materials Nos. 1, 2, 5 and 13-15 had excellent wear resistance with pin wear diameters of 1.00 μm or less after the wear test. These crankshaft materials had excellent machinability with flank wear of the cutting tool of 0.040 mm or less.

[0078] The crankshaft materials No. 3 and No. 6 had poor machinability. This was probably due to the low volume fraction of pro-eutectoid ferrite. The low volume fraction of pro-eutectoid ferrite was probably due to Fn1 being too large.

[0079] The No. 4 crankshaft material had poor fatigue strength. This was probably due to the high volume fraction of pro-eutectoid ferrite. The high volume fraction of pro-eutectoid ferrite was probably due to Fn1 being too small.

[0080] The No. 7 crankshaft material had poor machinability. This was probably due to the low volume fraction of pro-eutectoid ferrite. The reason for the low volume fraction of pro-eutectoid ferrite was probably due to the heating time during die forging being too long.

[0081] The No. 8 crankshaft material had poor wear resistance. This was due to the Mn θ / C θ This is probably because the Mn θ / C θ The reason for the low value is thought to be that the heating temperature during billet forging was too low.

[0082] The crankshaft materials No. 9 and No. 10 had poor wear resistance. This was due to the Mn θ / C θ This is probably because the Mn θ / C θ The reason for the low value is thought to be that no forging was performed when manufacturing the billet.

[0083] The No. 11 crankshaft material had poor wear resistance. This was due to the Mn θ / C θ This is probably because the Mn θ / C θ The reason for the low value is believed to be that the holding time during billet forging was too short.

[0084] The No. 12 crankshaft material had poor wear resistance. This was due to the Mn θ / C θ This is probably because the Mn θ / C θ The reason for the low value is thought to be that the cooling rate during die forging was too fast.

[0085] Fig. 1 is a scatter diagram showing the relationship between Fn1 and the pro-eutectoid ferrite volume fraction Fα, created from nine pieces of data (Nos. 1-6 and 13-15) in which the billet forging process code is "a1" and the die forging process code is "a2". Fig. 2 is a scatter diagram showing the relationship between Fn1 and the amount of flank wear, created from eight pieces of data excluding No. 6, in which the cutting tool was broken, out of the nine pieces of data in Fig. 1. It can be seen from Figs. 1 and 2 that there is a strong correlation between Fn1 and the pro-eutectoid ferrite volume fraction, and between Fn1 and the amount of flank wear.

[0086] Although one embodiment of the present invention has been described above, the above-described embodiment is merely an example for carrying out the present invention. Therefore, the present invention is not limited to the above-described embodiment, and the above-described embodiment can be appropriately modified and carried out within the scope of the invention.

Claims

1. A crankshaft blank, comprising: The chemical composition, in mass%, is C: 0.35-0.50%, Si: 0.75-2.50%, Mn: 1.00-1.50%, Cr: 0.30% or less, P: 0.030% or less, S: 0.020-0.100%, Al: 0.500% or less, N: 0.002 to 0.020%, V: 0 to 0.20%, Ti: 0 to 0.050%, Ca: 0-0.010%, The balance is Fe and impurities. Fn1 defined by the following formula (1) is 5.10 or more and 6.00 or less, The structure contains 5.0 to 18.0 volume % pro-eutectoid ferrite and the remainder is pearlite, The Mn content Mn obtained by analyzing the cementite in the pearlite by energy dispersive X-ray analysis at a depth of 50 μm from the surface of the part corresponding to the pin part of the crankshaft θ and C content C θ Ratio of Mn θ / C θ A crankshaft blank having a tensile strength of 0.36 or more. Fn1=7C+0.5Si+Mn+3Cr-10Ti (1) In formula (1), C, Si, Mn, Cr, and Ti are substituted with the contents of the corresponding elements in mass %. The energy dispersive X-ray analysis is carried out on C, Mn, Cr, V and Fe. θ and C θ Each of the above is a value calculated in mass % with the sum of C, Mn, Cr, V and Fe as the denominator.

2. 2. The crankshaft blank according to claim 1, A crankshaft material that satisfies the following formula (2): Fα<0.875×Si+14.344 (2) In formula (2), the volume fraction of pro-eutectoid ferrite in % is substituted for Fα, and the content of Si in mass % is substituted for Si.

3. 2. The crankshaft blank according to claim 1, A crankshaft material that satisfies the following formula (3): Fα<-16.059×Fn1+112.0 (3) In formula (3), the volume fraction of pro-eutectoid ferrite is substituted for Fα in percentage.

4. A method for producing the crankshaft blank according to any one of claims 1 to 3, comprising the steps of: a billet forging process in which the slab produced by the continuous casting process is hot forged into a billet; and a die forging step of hot forging the billet. In the hot forging in the billet forging step, the heating temperature before the hot forging is 1150 to 1300° C., and the holding time at the heating temperature is 3.0 hours or more; In the hot forging in the die forging step, a heating temperature before hot forging is 1200 to 1350°C, a heating time up to the heating temperature is 500 seconds or less, and an average cooling rate in a temperature range of 750 to 600°C after forging is 0.5°C / second or less.

Citation Information

Patent Citations

  • Steel for machine structure excellent in machinability and toughness, and machine structural parts

    JP2000282172A

  • Steel for machine structural use and machine structural part excellent in machinability

    JP2001214241A

  • Non-heat-treated steel for hot working having excellent wear resistance and hot worked product

    JP2003201536A